Analysis of the Economic Feasibility of Using Modern Agricultural Machinery in Oil Palm Plantations in South Sumatra - Judijanto, Loso (West Science Agro, 2024)
This study investigates the economic feasibility of using modern agricultural machinery in oil palm plantations in South Sumatra. A quantitative approach was employed, involving 40 samples collected through a structured questionnaire utilizing a Likert scale from 1 to 5. The data were analyzed using SPSS version 26, focusing on key economic indicators such as production efficiency, cost savings, and profitability. The results revealed strong positive and significant relationships between the use of modern machinery and all three economic indicators. The findings suggest that modern agricultural machinery significantly enhances economic performance in oil palm plantations, making it a viable investment for improving productivity and profitability. These insights provide valuable guidance for plantation owners and policymakers in promoting the adoption of advanced agricultural technology in the region.